Respiratory Barrier as a Safeguard and Regulator of Defense Against Influenza A Virus and Streptococcus pneumoniae - LeMessurier, Kim S.; Tiwary, Meenakshi; Morin, Nicholas P.; Samarasinghe, Amali E. (Frontiers in Immunology, 2020)
The primary function of the respiratory system of gas exchange renders it vulnerable to environmental pathogens that circulate in the air. Physical and cellular barriers of the respiratory tract mucosal surface utilize a variety of strategies to obstruct microbe entry. Physical barrier defenses include the surface fluid replete with antimicrobials, neutralizing immunoglobulins, mucus, the rapidly beating cilia, and epithelial cell layer that forms a near impenetrable wall that separates the external environment from the internal soft tissue of the host. Resident leukocytes primarily of the innate immune branch also maintain the integrity of the airways by constant surveillance and maintenance of homeostasis through the release of cytokines and growth factors. Unfortunately, pathogens such as influenza virus and Streptococcus pneumoniae require hosts for their replication and dissemination and prey on the respiratory tract as an ideal environment causing severe damage to the host during their invasion. In this review, we outline the host-pathogen interactions during influenza and post-influenza bacterial pneumonia with a focus on inter- and intra-cellular crosstalk important in pulmonary immune responses.